2003
DOI: 10.1074/jbc.m309156200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymerase II Processivity on Alternative Splicing Depends on Splice Site Strength

Abstract: Transcription and pre-mRNA splicing are coordinated temporally and spatially, and both processes can influence each other. In particular, control of transcriptional elongation by RNA polymerase II has proved to be important for alternative splicing regulation. In this report we demonstrate that the efficiency of exon recognition by the splicing machinery is crucial for the elongation control. Alternative splicing of the fibronectin extra domain I (EDI) is because the polypyrimidine tract of its 3-splice site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…The association patterns we observed shed new light on past evidence that indicated that RNA processing as well as RNA processing factors can alter transcription elongation rates (EnriquezHarris et al 1991;Cramer et al 1999;Kadener et al 2002;de la Mata et al 2003;Howe et al 2003;Nogues et al 2003;Proudfoot 2003;Robson-Dixon and Garcia-Blanco 2004;Ujvari and Luse 2004). On internal exons, PTBP1 and CSTF2 exhibited relatively homogeneous and strong enrichment around the center of exons while RNA Pol II had a broader enrichment both 5Ј and 3Ј from the center of the exon.…”
Section: Rna Binding Proteins Have Distinct Interaction Patterns Acromentioning
confidence: 82%
“…The association patterns we observed shed new light on past evidence that indicated that RNA processing as well as RNA processing factors can alter transcription elongation rates (EnriquezHarris et al 1991;Cramer et al 1999;Kadener et al 2002;de la Mata et al 2003;Howe et al 2003;Nogues et al 2003;Proudfoot 2003;Robson-Dixon and Garcia-Blanco 2004;Ujvari and Luse 2004). On internal exons, PTBP1 and CSTF2 exhibited relatively homogeneous and strong enrichment around the center of exons while RNA Pol II had a broader enrichment both 5Ј and 3Ј from the center of the exon.…”
Section: Rna Binding Proteins Have Distinct Interaction Patterns Acromentioning
confidence: 82%
“…If, however, elongation is fast and a weak and strong splice sites become available more or less simultaneously, the splicing machinery will favor the strong splice site over the weak splice site. Several examples of this phenomenon exist, 44,45 but the most compelling evidence is provided by the use of mutant slow Pol II, resulting in a slower elongation rate and altered exon usage of fibronectin. 46 The fact that Pol II elongation rates influence alternative splicing has led to the hypothesis that epigenetic modifications could also influence alternative splicing because these modifications can influence chromatin structure and therefore the elongation rate of Pol II.…”
Section: Regulation Of Splicingmentioning
confidence: 99%
“…By mutating EDI's polypyrimidine tract and therefore generating pre-mRNAs with increasing degrees of exon recognition, it was shown that responsiveness of exon skipping to elongation is inversely proportional to the 3Ј-splice site strength, which means that the better the alternative exon is recognized by the splicing machinery, the less its degree of inclusion is affected by transcriptional elongation (Nogués et al 2003).…”
Section: Pol II Elongationmentioning
confidence: 99%